Using The Problem-Based Learning (PBL) Role-Play Method to Improve Learning Outcomes in Pancasila Education Subject - Rada Rahmawati; Abd Rahman Azhari; Roso Sugiyanto; Ichyatul Afrom (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: This study was motivated by the low learning outcomes of fourth-grade students in the Pancasila Education subject at SDN 2 Panarung. Preliminary observations indicated that students experienced difficulties in understanding the learning material, resulting in low achievement of the Minimum Mastery Criteria (MMC). Aim:  This study aimed to examine the effectiveness of implementing a roleplay method based on the Problem-Based Learning (PBL) model to improve students’ learning outcomes. Method: The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects were 15 fourth-grade students. Data were collected using learning outcome tests in the form of pre-tests and post-tests consisting of 20 multiple-choice questions related to the Pancasila Education material on unity and solidarity in diversity. The data were analyzed descriptively by calculating the average score and the percentage of students who achieved the MMC. The results showed that only 13% of students achieved the MMC in the pre-test, while 87% did not. After the implementation of the action in Cycle I, the percentage of students achieving mastery increased to 60%. Further improvement in Cycle II resulted in all students (100%) achieving the MMC. Result and Discussions: These findings indicate that integrating the roleplay method into the PBL model can support students’ understanding of learning material and improve cognitive learning outcomes. Conclusion, the implementation of the roleplay method based on the PBL model was effective in improving the learning outcomes of fourth-grade students in Pancasila Education within the context of Classroom Action Research. However, this study was limited to one class and focused only on short-term cognitive outcomes. These findings provide practical evidence for elementary school teachers to integrate roleplay into PBL-oriented instruction to enhance cognitive learning outcomes.